2020
DOI: 10.1007/s12524-020-01219-z
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Carotenoid Pigmentation due to Haloarchaea Microbes in the Lonar Lake, Maharashtra, India Using Sentinel-2 Images

Abstract: The Lonar Lake of Maharashtra is a crater based-saline lake. During the month of June 2020, this lake suddenly changed its colour and turned to pink due to the presence of Haloarchaea microbes, and this species have a unique adaptation style to survive in high saline condition. The salinity of this lake is increasing due to less rainfall, low human intervention, and an increase in the temperature of this region. These microbes produce fantastic bloom, which can be sensed from outer space because of red-orange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…S2A and S2B were commissioned in orbit in 2015 and 2017, respectively. The important usage for S2 images has been in studying lake ecology and water quality parameter estimation at a finer scale (Bresciani et al 2018 ; Bhattacharjee et al 2020 ). The temporal resolution of the S2A imager is 10 days, but it gets reduced to 5 days when both the sensors are operational.…”
Section: Methodsmentioning
confidence: 99%
“…S2A and S2B were commissioned in orbit in 2015 and 2017, respectively. The important usage for S2 images has been in studying lake ecology and water quality parameter estimation at a finer scale (Bresciani et al 2018 ; Bhattacharjee et al 2020 ). The temporal resolution of the S2A imager is 10 days, but it gets reduced to 5 days when both the sensors are operational.…”
Section: Methodsmentioning
confidence: 99%
“…The Lonar Lake water had turned pink during June 2020 due to the presence of Haloarchaea microbes (Fig. 7 ) (Bhattacharjee et al, 2021 ; Ali and Ali, 2021 ). Several media reported this event of 11th June 2020; however, a similar color change of water from green to brown was observed in June 2019 also.…”
Section: Ecological Importance Of the Lonar Impact Cratermentioning
confidence: 99%
“…In 2020, it was prominent owing to the color change from green to brown to pinkish red (Mishra et al, 2021 ). Bhattacharjee et al ( 2021 ) used Sentinel-2 datasets from January 2020 to June 2020 and found out that the microbial bloom might have occurred between May 31 and June 5 with the help of several calculated indices. The red–orange carotenoids produced by the microbes give the water a pink tint that was even detectable from outer space.…”
Section: Ecological Importance Of the Lonar Impact Cratermentioning
confidence: 99%
See 2 more Smart Citations